The Effect of Size on Financial Performance of Commercial Banks in Kenya - Mirie Mwangi (European Scientific Journal, ESJ, 2018)
The question of whether size influences financial performance of commercial banks has not been conclusively settled empirically. The objective of the study was therefore to establish the effect size has on the profitability of commercial banks in Kenya. The study used an unbalanced panel of all commercial banks in Kenya for the ten year period 2007 to 2016 (the number ranged from 39 to 43). Regression analysis was used to relate size (proxied by log of total assets) against financial performance (Return on assets and return on equity). Size was found to have a positive effect on financial performance of commercial banks in Kenya. In addition, the effect was stronger the larger the commercial bank. The study recommends that policy initiatives geared towards increasing the size of the commercial banks be considered and shareholders/managers could also adopt growth strategies (internally generated, fund raising or mergers and acquisitions).